Designing smelter industry investment competitiveness policy in Indonesia through system dynamics model. Issue 3 (28th June 2019) - Hanafi, Muhammad; Wibisono, Dermawan; Mangkusubroto, Kuntoro; Siallagan, Manahan; Badriyah, Mila Jamilah Khatun
Abstract : Purpose: This research aims to examine the smelter industry's investment competitiveness in Indonesia as well as to find solutions to improve its competitive advantage for the nation. Design/methodology/approach: This research applies a sequential mixed-methods approach with a second quantitative phase building on an initial first qualitative phase. The qualitative phase is conducted by interviews to find the root causes of problems as well as solutions to gain smelter industries' competitiveness. The quantitative phase is conducted by a system dynamics model. A descriptive causal loop diagram is created based on interviews and focus group discussions to describe the problems. The concept of competitive advantage of a nation from Porter's diamond model is applied in this research. Findings: The results reveal the complexity of smelter industries in Indonesia. The paper also addresses the causes of problems and interaction of variables using a causal loop diagram. To gain the smelter industry's competitiveness, this paper suggests the potential policy development to increase competitiveness of the smelter industry such as policy for different fiscal incentives to each different mineral, effective export duty and exploration obligation. Practical implications: The result of this study provides a good basis for government in making policy to improve the competitive advantage of the smelter industry investment in Indonesia. Originality/value: This is the first research on smelter industry competitiveness that applies Porter's diamond model and system dynamics model to find solutions in designing appropriate policy to gain competitiveness.